2023
DOI: 10.1515/psicl-2022-1020
|View full text |Cite
|
Sign up to set email alerts
|

Thematic role mappings in metaphor variation: contrasting Englishbakeand Spanishhornear

Abstract: The present study investigates the scope of metaphors evoked by the culinary term bake in American English and its Peninsular Spanish equivalent hornear. The data analysed was extracted from the Corpus of Contemporary American English and the Corpus del Español: Web/Dialects. The target frames evoked and the frame elements involved in the metaphorical mappings were used to identify and analyse the metaphorical expressions. Furthermore, the type of process and thematic roles performed by the frame elements in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Furthermore, stewing can express drug intoxication. In this regard, the results indicate that stewing solely refers to alcohol intoxication, as opposed to other cooking frames like baking, which usually refers to marijuana consumption (Esbrí-Blasco, Navarro i Ferrando, 2023).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Furthermore, stewing can express drug intoxication. In this regard, the results indicate that stewing solely refers to alcohol intoxication, as opposed to other cooking frames like baking, which usually refers to marijuana consumption (Esbrí-Blasco, Navarro i Ferrando, 2023).…”
Section: Discussionmentioning
confidence: 86%
“…The metaphorical senses identified in COCA and CEWD have been compared in both languages, thereby bringing to light the similarities and divergencies in terms of metaphorical conceptualisation across cultures. The metaphor analysis is based on comparing conceptual mappings between the SF and the TFs (see Esbrí-Blasco, Navarro i Ferrando, 2023). This study addresses the limitations identified in prior research by offering a cross-linguistic, in-depth, systematic analysis of the particular FEs participating in metaphorical correspondences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations